Can bladder endometriosis be hard to diagnose? A two-case report and literature review - Li, Xingchen; Li, Hong (Frontiers in Medicine, 2025)
ObjectivesBladder endometriosis (BE) is an uncommon form of deep infiltrating endometriosis (DIE). This report aims to present two cases of BE with markedly contrasting clinical histories and presentations to highlight diagnostic challenges and discuss management strategies.MethodsWe describe the clinical presentation, diagnostic workup including pelvic magnetic resonance imaging (MRI), surgical management (laparoscopic partial cystectomy), histopathological findings, and short-term follow-up of two young women diagnosed with BE. Relevant literature is reviewed to contextualize the findings.ResultsBoth patients were accurately diagnosed preoperatively via MRI and underwent successful laparoscopic partial cystectomy, with histopathology confirming BE. Postoperative management involved a sequential protocol of gonadotropin-releasing hormone agonists (GnRH-a) followed by dienogest, which resulted in favorable short-term results, with no recurrence noted during follow-up.ConclusionDiagnosing BE is often straightforward when typical clinical and imaging findings align. However, diagnostic delays are common due to the condition’s rarity and symptom overlap. Early diagnosis is crucial for achieving better outcomes. For women of reproductive age experiencing recurrent pelvic symptoms, even atypical ones, early pelvic imaging examinations are recommended. MRI plays a key role in diagnosing BE, guiding treatment decisions, and assisting with differential diagnosis. Enhancing awareness of BE among clinicians and radiologists is essential to expedite diagnosis and treatment.